Uncertainty and Status‐Based Asymmetries in the Distinction Between the "Good" Us and the "Bad" Them: Evidence That Group Status Strengthens the Relationship Between the Need for Cognitive Closure and Extremity in Intergroup Differentiation. (9th September 2013) - Federico, Christopher M.; Hunt, Corrie V.; Fisher, Emily L.
Abstract : In this article, we look at how a key index of discomfort with uncertainty—the need for cognitive closure—interacts with perceived group status to influence a key antecedent of extremism: intergroup differentiation. Because high status provides people with a clear basis for superiority claims, we predicted that individuals with a high need for closure would accentuate intergroup differences in favor of the ingroup when they believe the latter to have higher status relative to outgroups. Two studies provided support for this hypothesis. In Study 1, Whites who were high in need for closure differentiated in favor of the ingroup when they perceived a larger status difference between the high‐status ingroup and lower‐status Black and Latino outgroups. In Study 2, individuals high in need for closure who were randomly assigned to a high‐status (vs. low‐status) group displayed the same pattern.